Rage and protests across the country - MacCarald, Clara, 1979- (Understanding the Black Lives Matter movement., 2021)
Explores the Black Lives Matter movement which protests needless killings of persons of color by law enforcement officers. Highlights high-profile cases and documents Black Lives Matter protest responses. Includes color photographs, sidebars, a glossary, and additional resources.